2018
DOI: 10.4103/jfmpc.jfmpc_318_17
|View full text |Cite
|
Sign up to set email alerts
|

Patients satisfaction with consultation at primary health care centers in Abha City, Saudi Arabia

Abstract: Aim of Study:This study aims to assess patients satisfaction regarding consultations at the General Clinics of primary health-care (PHC) centers, in Abha City.Patients and Methods:This cross-sectional study design was conduct among adult patients attending training PHC centers in Abha City, Saudi Arabia during September 2016. The researcher designed a data collection sheet that comprised patients’ personal characteristics and the consultation satisfaction questionnaire, which contained 18 questions within four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 15 publications
1
21
3
3
Order By: Relevance
“…Some divergent aspects were also noted. Contrary to previous ndings, [18,19,20] this study found that patients with lower levels of education tended to be more dissatis ed with the service.…”
Section: Discussioncontrasting
confidence: 99%
“…Some divergent aspects were also noted. Contrary to previous ndings, [18,19,20] this study found that patients with lower levels of education tended to be more dissatis ed with the service.…”
Section: Discussioncontrasting
confidence: 99%
“…Such associations were observed in other Saudi PHCs. 6,7 Interestingly, neither the monthly income nor the number of family members were associated with the overall satisfaction score. A possible contributing factor to this may that PHC services in Saudi Arabia are delivered free of charge and are entirely covered by the government.…”
Section: Discussionmentioning
confidence: 96%
“…Such associations were observed in other Saudi PHCs. 6 , 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the index patient denied he had travelled to Saudi Arabia, many citizens of South Korea were more open about their condition and travel during subsequent contact tracing and had a good relationship with the health care professionals in their community [56]. This is due to better universal health coverage, and flexibility to choose health care professionals compared to Saudi Arabia, where the government has more restrictions and involvement in healthcare decisions [56,57]. From the beginning of the outbreak, South Korean patients who were MERS-positive sought and embraced medical attention much faster than did Saudi Arabian patients [58].…”
Section: Aspect 1 -Public Information and Quarantine/isolation Practicesmentioning
confidence: 99%